The Influence of Institutional Policies and Information Technology Adoption towards Sustainable Logistics Transportation - Nur Fadiah Mohd Zawawi; Sazali Abd Wahab; Suzana Idayu Wati Osman; Ahmad Shaharudin Abdul Latiff; Syed Ali Fazal (International Journal of Supply Chain Management, 2018)
Logistics is the movement engine for cargos and merchandises both for domestics and international. People complete their business process through logistics transportation, especially to move cargos and merchandises reaching their end users around the world, hence transportation also can be considered as the backbone to business supply chain. Unfortunately, their operations produced negative impacts to our environment and society. Thus, business activities nowadays goes beyond sustaining economic sustainability solely. They are concern dearly on the environmental quality and human well-being as well. The objective of this paper is to review the influence of institutional policies and information technology (IT) adoption towards sustainable logistics transportations in the economic, environmental and social performance. Through understanding of Institutional Theory and Resource-Based View (RBV) Theory, institutional policies and IT adoption can be considered as the enabler for logistics performance and their sustainability. This paper expects to provide new insights to the logistics practitioners and policy makers in sustaining logistics sector in parallel with todays world demand, Sustainable Development Goals (SDGs).